Induksi Kalus Dari Eksplan Daun Tanaman Kawista (Limonia Acidissima L.) Melalui Pemberian Kombinasi Naphthalene Acetic Acid (NAA) - Muh. Yogi Fauzi; Hayatul Rahmi; Ani Lestari (Universitas Respati Indonesia, 2025)
Kawista (Limonia acidissima L.) is a nutrient-rich tropical plant with antioxidant, anticancer, antidiabetic, and anti-inflammatory benefits. Despite its usefulness, it remains rare due to slow growth—taking up to 15 years to bear fruit. In regions like Rembang and Karawang, it is used in traditional foods and drinks. Tissue culture offers a faster, more efficient method for kawista propagation. This research aimed to determine the optimal concentration combination of Naphthalene Acetic Acid (NAA) and Benzyl Amino Purine (BAP) for promoting callus growth from kawista (Limonia acidissima L.) leaf explants through tissue culture techniques. The study was conducted at the Plant Biotechnology Laboratory, Academic Support Unit (UPA), University of Singaperbangsa Karawang, from February to March 2025.mThe experimental method employed a Completely Randomized Design (CRD) with a single factor involving various concentration combinations of NAA and BAP. The treatments consisted of six combinations, each replicated five times: A (control), B (1 ppm NAA + 5 ppm BAP), C (3 ppm NAA + 5 ppm BAP), D (5 ppm NAA + 5 ppm BAP), E (7 ppm NAA + 5 ppm BAP), and F (9 ppm NAA + 5 ppm BAP). The results demonstrated that the combination treatments significantly affected callus initiation time, callus growth percentage, callus diameter, and callus weight. The most effective treatment was F (9 ppm NAA + 5 ppm BAP), which showed the shortest average time for callus emergence 14.87 days, the largest average callus diameter 1.66 cm, and the highest average callus weight 0.39 gram.